miR-495-3p promotes chronic obstructive pulmonary disease by activating ferroptosis in lung epithelial cells through regulation of the ETS1/GPX4 axis - Hongbo Chen; Yungui Tu; Lina Wang; Simeng Zhu (Molecular Biology Reports, 2026)

Repeated long-term cover cropping and nitrogen fertilization enhance soil multifunctionality - Lin Li; Wanyu He; Qilong Du; Xue Zhao; Minghui Meng; Guangjin Wu; Guangxi Liu; Simeng Wang; Jun Wang; Fazhu Zhao; Jieying Wang (Agriculture, Ecosystems & Environment, 2026)

Rapid screening method of glucocorticoid residues in sample-limited cell-cultured meat - Peiwen Yu; Simeng Li; Chen Zhang; Xiaohui Li; Hongping Wang; Fen Jin (Food Research International, 2026)

Adaptive laboratory evolution of Lactiplantibacillus plantarum for enhanced lactose metabolism: Phenotypic changes and underlying molecular mechanisms - Hong Li; Simeng Wang; Jiao Wu; Xingyu Li; Ruihang Liu; Yuenan Wang; Tong Dan (Food Research International, 2026)

A novel conformationally constrained RGD-based cyclic peptide targeting integrin αvβ6 protein for antitumor therapeutic applications - Yang Lv; Chunyu Qu; Yue Lei; Hongrui Zhang; Zeyan Jiang; Simeng Zhao; Tingting Li; Xiaodan Wu; Zhiqiang Wang (Chemico-Biological Interactions, 2026)

Warming attenuates root-induced decomposition enhancement via soil moisture limitation in a subtropical forest of China - Shuai Liu; Simeng Wang; Yuxiang Xu; Xiangliang Li; Qianqian Xi; Chuansheng Wu (Acta Oecologica, 2026)

Disrupting KRAS–AGO2 interaction: a dual-pronged strategy to sensitize chemo-immunotherapy in KRAS-mutated colorectal cancer - Jingyi Xie; Simeng Wang; Juan Liu; Yan Zhang; Haixiao Zhu; Rongrong Cui; Yao Yao; Wei Yu; Peng Hou (Apoptosis, 2026)

The mixed cover crops and nitrogen fertilization decrease the soil microbial dormancy - Simeng Wang; Xue Zhao; Wanyu He; Jieying Wang; Minghui Meng; Xiya Xiong; Min Xie; Guangjin Wu; Qilong Du; Lin Li; Guangxi Liu; Jun Wang; et al. (Plant and Soil, 2026)

Evolution of mid-late Holocene fire dynamics and its driving mechanisms: Evidence from Balikun Lake, Xinjiang, China - Panpan Cui; Wen Li; Yuqin Zhou; Yingqiu Gao; Simeng Wang (Quaternary International, 2026)

Unintentional Weight Loss as a Predictor of Adverse Prognosis in Older Adults With Chronic Obstructive Pulmonary Disease in the Intensive Care Unit: A Retrospective Cohort Study - Hongtao Cheng; Yonglan Tang; Shanyuan Tan; Simeng Song; Jia-Ming Xiong; Xiaxuan Huang; Yitong Ling; Zichen Wang; Fuling Zhou; Jun Lyu (Journal of the Academy of Nutrition and Dietetics, 2026)

Microplastics enter strawberry fruit tissues directly through the epidermis - Chen Zhang; Simeng Li; Hongping Wang; Xiaohui Li; Lihui An; Fen Jin (Journal of Hazardous Materials, 2026)

Metagenomic analysis of lactic acid bacteria communities in inner Mongolian fermented dairy products: influence of milk source and geography - Hong Li; Haimin Hu; Wenhui Lu; Jinhui Liu; Qingting Peng; Simeng Wang; Tong Dan (Food Research International, 2026)

Sex-dependent acute oral toxicity and in vivo distribution of 6:2 chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFESA) in rats - Simeng Li; Peiwen Yu; Bowen Li; Xiaohui Li; Hongping Wang; Fen Jin (Food and Chemical Toxicology, 2026)

An efficient embryogenic cell suspension enabling somatic embryogenesis in Phyllostachys edulis - Simeng Kong; Huan Liu; Kaiting Wang; Xiaohong Zhou; Xinyi Yang; Juan Zhuo; Xiangyu Li; Xinchun Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

A new strain of Trichoderma shows improved biocontrol of Fusarium root rot in ginseng via functional metabolites, defense induction and rhizosphere regulation - Simeng Zhao; Liwei Wang; Chao Li; Zhangxin Hou; Xinping Yang; Hongyan Yang (Rhizosphere, 2026)

Comparative genomics reveals population structure and ecological adaptation in Lactobacillus helveticus - Haimin Hu; Jiao Wu; Jiaqi Sun; Simeng Wang; Jinhui Liu; Tong Dan (Food Research International, 2026)

Two-step interfacial polymerization for bilayer polyamide membranes with a gradient-density structure and enhanced desalination performance - Simeng Wang; Yi Wei; Mengqi Ma; Kaiyu He; Bo Wang (Desalination, 2026)

Insights into the phosphate stabilization and removal mechanism enabled by phosphogypsum-fly ash ceramsite - Simeng Gan; Zhaorui Li; Yunkang Zhang; Fei Wang; Xiaofeng Huang; Yixing Ma; Quxiu Dai; Ping Ning; Kai Li; Xin Sun (Process Safety and Environmental Protection, 2026)

Long-term scenarios for climate adaptation of cotton crops in China, considering multidimensional biophysical and socio-economic scenario analysis - Simeng Guo; Fengqi Wu; Yuhan Wang; Jian Wang; Zhenggui Zhang; Zhanlei Pan; Chenxi Chong; Pengcheng Li; Weibin Huang; Guilan Sun; Xin Li; Shuchen Wang; et al. (Journal of Cleaner Production, 2026)

The magnetic characteristics of surface soils in Nanchang City, China, and their responses to heavy metal contamination - Gao Yingqiu; Li Wen; Wang Simeng; Zhou Yuqin; Cui Panpan (Environmental Geochemistry and Health, 2026)

Differential cannabinoid-like effects, receptor affinity and physiologically based pharmacokinetics of the synthetic cannabinoids 4F-MDMB-BINACA, 4F-MDMB-BICA and 5F-MDMB-PICA in mice: A comparative study - Yawen Xu; Simeng Zhang; Xuesong Shi; Lixin Kuai; Yuanyuan Chen; Kaixi Li; Xiangyu Li; Yanling Qiao; Dan Wang; Cheng Jiang; Peng Xu (Toxicology and Applied Pharmacology, 2025)

The sanitation in restrooms to respiratory health: modelling concentration distribution changes of bioaerosols across buildings with/without semi-open settings - Ting Zhang; Zuming Wang; Simeng Zhang; Yuying Chen; Guiying Li; Taicheng An (Environmental Pollution, 2025)

Feasibility of planting shrubs in arid areas from a water balance perspective - Chenguang Zhao; Chao Guan; Tengfei Yu; Jiazheng Wang; Huiying Li; Xia Wang; Baojun Zhang; Simeng Kou; Xuejuan Liu; Changming Zhao (Journal of Hydrology, 2025)

Oral administration of large-leaf yellow tea protein-derived oligopeptides alleviates UV-induced skin photoaging through the inhibition of MAPK/AP-1/MMP9 signaling pathway - Ziyi Shen; Simeng Zhou; Yaru Zhang; Yuan Zhang; Hongyan Wang; Daxiang Li; Yijun Wang; Zhongwen Xie; Huifang Ge (Food Research International, 2025)

Deep eutectic solvents molecular interfacial engineering for suppressing chemical corrosion in Li metal batteries - Simeng Wang; Hongtao Li; Caiwen Zhao; Pengtao Guo; Minting Luo; Yu Liang; Jiajia Huang; Shimou Chen (Chemical Engineering Journal, 2025)

SERS detection of lung cancer-related volatiles in exhaled breath utilizing size controllable Au NC@ZIF-8 core-shell nanoparticles - Zixuan Wang; Wei Ran; Juan Shen; Yuanyuan Cao; Zhongzhong Wang; Simeng Zhang; Rongzhang Hao (Chemical Engineering Journal, 2025)

Naphthenic acids (NAs) - tolerant aerobic granular sludge: Removal performance, degradation mechanism, and microbial response - Jin Li; Shasha Liu; Simeng Li; Jiayu Song; Qinghong Wang; Chunmao Chen (Journal of Environmental Management, 2025)

Changes in Physiological Characteristics of Rye Treated with 2,4-Epibrassinolide Under Combined Stress of Cd and Freeze-Thaw - Lingzhi Tian; Guozhang Bao; Huixin Wang; Yanan Xu; Simeng Chen; Yunqi Jiang; Guomei Li (Water, Air, & Soil Pollution, 2025)

Climate change influences on algal bloom intensity in lakes in the Yangtze River Basin, China from 1985 to 2022 - Simeng Wang; Boqiang Qin; Boqing Wen; Chang Huang (Journal of Hazardous Materials, 2025)

Comprehensive insights into oil absorption in fried foods: The role of surface characteristics - Shuangyi Zhang; Zhiguo Gong; Simeng Wang; Shuli Zhao; Wei Mao; Bo Liu; Ying Liu (Food Chemistry, 2025)

Osthole–pyrethrins combination loaded onto hollow microsphere silica nanoparticles inhibits Fusarium solani growth and controls root rot incidence in Cynanchum auriculatum - Xiaomeng Fei; Bing Xie; Junjie Tang; Lixia Wang; Yong Zheng; Haifeng Kuai; Simeng Li; Daoguo Zhang; Wei Gu (Physiological and Molecular Plant Pathology, 2025)

Quantitative source apportionment of surface ozone in Liaoning Province, China, under the Asian summer monsoon background - Ningwei Liu; Simeng Ma; Kun Wang; Sen Yang; Zhigang Zhang (Atmospheric Pollution Research, 2025)

Revealing considerable emissions reduction potential in flight operations: A real-time emission perspective - Simeng Ma; Shizhuo Lin; Bo Han; Chen Zhang; Zhiqiang Wei; Lingxiang Xue; Jingbo Zhao; Kun Wang; Jian Yu; Philip K. Hopke (Transportation Research Part D: Transport and Environment, 2025)

Tracing the carbon footprint of cotton garments from seed to garment: Evidence from an empirical study of multiple sites in China - Shuchen Wang; Chenxi Chong; Weibin Huang; Simeng Guo; Yuhan Wang; Yaopeng Zhang; Zhanlei Pan; Jian Wang; Xin Li; Wenqi Zhao; Zhenggui Zhang; Zhanbiao Wang (Resources, Conservation and Recycling, 2025)

Exogenous γ-aminobutyric acid (GABA) effectively alleviates the synergistic inhibitory effect of freeze-thaw and copper combined stress on rye seedling growth - Huixin Wang; Guozhang Bao; Lingzhi Tian; Simeng Chen; Yanan Xu; Guomei Li (Journal of Environmental Management, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Dissipation patterns of trisiloxane ethoxylates in cucumber plants and field soils: Insights from different end-capping groups - Simeng Li; Xiaohui Li; Chen Zhang; Bowen Li; Peiwen Yu; Qin Dai; Hongping Wang; Fen Jin (Journal of Hazardous Materials, 2025)

Assessment of the mechanism of combined toxicity of imidacloprid and triadimefon to Secale cereale L. seedlings under freeze-thaw cycle conditions - Simeng Chen; Guozhang Bao; Yanan Xu; Huixin Wang; Lingzhi Tian; Jinke Hu; Zhaoxing Wu; Kaino Yano.W (Journal of Environmental Management, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

High strength, gas barrier and hydrophobic konjac glucomannan/glutenin films with semi-interpenetrating network for cherry tomato preservation - Pengpeng Deng; Zihao Wang; Yuewen Li; Simeng Ji; Yufei Sun; Qianxi Deng; Juanjuan Chen; Fatang Jiang (Food Hydrocolloids, 2025)

Plant polyphenols as natural bioactives for alleviating lipid metabolism disorder: Mechanisms and application challenges - Haiying Wei; Jinsheng Rui; Xinke Yan; Ruyan Xu; Simeng Chen; Baiming Zhang; Lei Wang; Zhisong Zhang; Chengwen Zhu; Mengtao Ma; Huining Xiao (Food Research International, 2025)

Necroptosis in obesity: a complex cell death event - Zunhai Liu; Simeng Wang; Wentao Wang; Rui Lv; Chao Sun (Apoptosis, 2025)

Self-Compensating strategy of electronic Structure-Modulated selenide @ carbon nanotube / carbon nanofiber for High-Efficiency electromagnetic wave absorption and corrosion resistance - Simeng Wu; Yanxiang Wang; Jiangyiming Jiang; Yibo Li; Dongming Liu (Chemical Engineering Journal, 2025)

Development and evaluation of the energy-saving effect of photothermal cooperative composite hydrogel smart window - Yang Zhou; Yiqi He; Simeng Qi; Sisi Zhao; Lulu Wang; Quan Xu (Chemical Engineering Journal, 2025)

Responses of magnetic properties to heavy metals pollution recorded by sediments of Nanchang City reach of Ganjiang River, East China - Simeng Wang; Wen Li; Changsheng Ye; Yingqiu Gao; Yuqin Zhou (Environmental Geochemistry and Health, 2025)

Distinctive Neural Substrates of low and high Risky Decision Making: Evidence from the Balloon Analog Risk Task - Zhenlan Jin; Simeng Li; Changan Wang; Xiaoqian Chai; Junjun Zhang; Ling Li (Brain Topography, 2025)

Unveiling the critical roles of nascent MnO2 in accelerating permanganate carbocatalysis - Jun Wang; Simeng Bi; Li Wei; Yi Shen; Fanpeng Meng; Yang Zhang; Xiaoyao Tan (Journal of Hazardous Materials, 2024)

Contribution of plastic solid components to volatile organic compounds formation during plastics combustion - Xinglei Wang; Simeng Tang; Ling Ding; Xinran Qiu; Zhenming Zhang; Li Xu; Xujun Liang; Xianfei Huang; Xuetao Guo (Journal of Hazardous Materials, 2024)

Effect of calcium chloride blanching combined with acetic acid soaking pretreatment on oil absorption of fried potato chips - Shuli Zhao; Simeng Wang; Qianru Lu; Ying Liu (Food Chemistry, 2024)

The relationship between starch synthesis enzyme activity, gene expression, and amylopectin fine structure in waxy maize - Haiyan Zhang; Fan Qin; Guanghai Xu; Simeng Geng; Yuan Yuan; Ming Wang; Fuchao Jiao; Jingtang Chen (Cereal Research Communications, 2024)

Exploring emission spatiotemporal pattern and potential reduction capacity in China's aviation sector: Flight trajectory optimization perspective - Simeng Ma; Xuan Wang; Bo Han; Jingbo Zhao; Zhongyi Guan; Jinlong Wang; Yufen Zhang; Baoshuang Liu; Jian Yu; Yinchang Feng; Philip K. Hopke (Science of The Total Environment, 2024)

Investigation of guanidino acetic acid and rumen-protected methionine induced improvements in longissimus lumborum muscle quality in beef cattle - Simeng Yi; Boping Ye; Jinze Wang; Xin Yi; Yao Wang; Abudusaimijiang Abudukelimu; Hao Wu; Qingxiang Meng; Zhenming Zhou (Meat Science, 2024)

Climate warming and nitrogen deposition had no significant interaction effect on litter decomposition of subtropical mountain forest in Southwest China - Yue Li; Simeng Wang; Ying Wang; Menglong Bu; Shuai Liu; Chuansheng Wu (Plant and Soil, 2024)

Inhibition of BCAT1 expression improves recurrent miscarriage by regulating cellular dysfunction and inflammation of trophoblasts - Guangli Xu; Chao Tian; Yanru Li; Lei Fang; Jing Wang; Zhuqing Jing; Simeng Li; Ping Chen (Cell and Tissue Research, 2024)

Maternal Supplementation of Collagen Peptide Chelated Trace Elements Enhances Skeletal Muscle Development in Chicks - Jiao Wang; Zhenwu Huang; Simeng Li; Zengpeng Lv (Biological Trace Element Research, 2024)

Large-leaf yellow tea protein derived-peptides alleviated dextran sodium sulfate-induced acute colitis and restored intestinal microbiota balance in C57BL/6 J mice - Huifang Ge; Fengxue Qi; Ziyi Shen; Hongyan Wang; Shangliang Zhu; Simeng Zhou; Zhongwen Xie; Daxiang Li (Food Chemistry, 2024)

Engineering PD-L1 targeted liposomal canagliflozin achieves multimodal synergistic cancer therapy - Simeng Wang; Mengjun Sui; Quan Chen; Jiahua Guo; Huini Yang; Ye Zhou; Meiju Ji; Yangyang Cheng; Peng Hou (Chemical Engineering Journal, 2024)

Exposure to volatile organic compounds and growth indicators in adolescents: Unveiling the association and potential intervention strategies - Jingyi Ren; Xiaoya Sun; Zhenao Zhang; Huanting Pei; Yadong Zhang; Rui Wen; Simeng Qiao; Zidan Wang; Weican Zhang; Jinshi Zuo; Yuxia Ma (Journal of Hazardous Materials, 2024)

One-step rapid removal of Cu(II) complexes via dual-active-site MOF catalysis with Peroxymonosulfate: Cooperative oxidation and adsorption - Shuo Wang; Simeng Guo; Xuedong Du; Ziqian Liu; Yujia Yang; Yaran Song; Qingrui Zhang (Chemical Engineering Journal, 2024)

Thyroglobulin as a Sensitive Biomarker of Iodine Status in Mildly and Moderately Iodine-Deficient Pregnant Women - Yujie Jiang; Simeng Gu; Zhe Mo; Xueqing Li; Chenyang Liu; Yahui Li; Guangming Mao; Yuanyang Wang; Fanjia Guo; Xiaoming Lou; Xiaofeng Wang (Biological Trace Element Research, 2024)
Pregnant women are more susceptible to iodine deficiency. However, there are limitations in existing indicators for the evaluation of iodine nutrition in pregnant women. The study aimed to explore whether thyroglobulin (Tg) can be used as a more sensitive biomarker for pregnant women with mild and moderate iodine deficiency. A repeated-measure study was conducted among 1332 pregnant women in Zhejiang Province, China. Serum and urine specimens were collected at a mean of 10, 17, and 32 weeks of pregnancy, respectively; thyroid-stimulating hormone (TSH), Tg, and urinary iodine concentrations were measured. Linear mixed effects models were used to determine the associations between interaction of iodine concentrations and increasing gestation week and TSH and Tg, where participants were divided by urinary iodine concentration (UIC). The median Tg concentration was 11.56, 11.45, and 12.43 μg/L in the first, second, and third trimesters, respectively. After controlling the covariates, the interaction effects between the iodine status and gestation week were significant for both TSH and Tg ( p = 0.038 and p = 0.007, respectively). TSH increased with the week of gestation in both iodine concentration groups. Tg increased with advancing pregnancy in the iodine-deficient group whereas it did not in the iodine-sufficient group. There was no significant variation in TSH at each trimester, and Tg was higher in the iodine-deficient group than in the iodine-sufficient group. Tg may be a more sensitive iodine status biomarker than TSH for pregnant women with mild-to-moderate iodine insufficiency.

A tumor-responsive nanostrategy for reducing the risk of immunotherapy-related myocarditis - Mengjun Sui; Simeng Wang; Ye Zhou; Hui Dang; Zekun Zeng; Kunrong Gu; Hongxin Cao; Meiju Ji; Penggao Dai; Yangyang Cheng; Peng Hou (Chemical Engineering Journal, 2024)

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

Dissipation and potential risk of tristyrylphenol ethoxylate homologs in peanuts by spraying and root irrigation: A comparative assessment - Hongping Wang; Minjie Li; Simeng Li; Xueying Chen; Bowen Li; Hua Shao; Fen Jin (Journal of Hazardous Materials, 2024)

Decreased Treg cells induced by bisphenol A is associated with up-regulation of PI3K/Akt/mTOR signaling pathway and Foxp3 DNA methylation in spleen of adolescent mice - Simeng Wang; Youdan Dong; Lingling Zhai; Yinglong Bai; Yilong Yang; Lihong Jia (Chemosphere, 2024)

Zinc oxide nanoparticles damage the prefrontal lobe in mouse: Behavioral impacts and key mechanisms - Dan Zhang; Zhiyuan Wang; Hongmei Deng; Simeng Yi; Tao Li; Xinjiang Kang; Jun Li; Chang Li; Tingting Wang; Bo Xiang; Guang Li (Toxicology Letters, 2024)

A comparative analysis of the puncturing abilities of cephalopod beak rostra using engineering tools - Simeng Wang; Marius Didziokas; Marjorie Roscian; Susan Evans; Isabelle Rouget; Anthony Herrel; Mehran Moazen; Louise Souquet (Marine Biology, 2024)
Cephalopods, a diverse class of carnivorous marine predators, exhibit a wide range of feeding behaviours and foraging strategies related to their lifestyle, habitat and morphological adaptations. Their beaks play a crucial role in capturing and processing prey. This study investigates the link between the shape of the rostrum of cephalopod beaks and their function through a mix of experimental and computational approaches. Fourteen upper beak rostrum models from a range of cephalopod species, representing their morphological and ecological diversity, were 3D-printed, and subjected to uniaxial puncture tests. Force and displacement were recorded to estimate puncture ability. Finite Element Analysis (FEA) was used to explore the form–function relationship under loading conditions mimicking biting and pulling, analysing stress patterns across different rostrum morphologies. The results show that rostrum size significantly influenced puncture performance, with smaller rostra requiring less force and displacement for puncturing. However, larger rostra exhibited higher structural stiffness, suggesting increased vulnerability to stress during biting. Morphology-driven tests demonstrated species-specific differences in puncture abilities, with rostrum sharpness playing a crucial role. FEA results further indicated that longer and sharper rostra were more susceptible to stress, potentially impacting their overall structural integrity. The findings highlight the trade-off between rostrum size and sharpness in cephalopod beaks, with implications for prey selection and feeding efficiency. The study contributes to understanding the morpho-functional aspects of cephalopod beaks and their role in prey capture and consumption, shedding light on the evolutionary pressures shaping these remarkable marine predators.

Bee colonies map the short- and medium-chain chlorinated paraffin contamination from the apiary environment - Shujun Dong; Suzhen Qi; Yazhou Zhao; Su Zhang; Xingyi Wu; Jun Cao; Yun Zou; Yuesen Wang; Simeng Xia; Peilong Wang; Liming Wu (Science of The Total Environment, 2024)

Comprehensive sensitivity analysis of the WRF model for meteorological simulations in the Arctic - Tong Zhang; Le Cao; Simeng Li; Chenchao Zhan; Jiandong Wang; Tianliang Zhao (Atmospheric Research, 2024)

Occurrence and distribution of trisiloxane ethoxylates in citrus orchard soils in China: Analytical challenges - Simeng Li; Ning Yue; Minjie Li; Xiaohui Li; Bowen Li; Hongping Wang; Jing Wang; Fen Jin (Science of The Total Environment, 2024)

Multi-model predictive control strategy for path-following of unmanned surface vehicles in wide-range speed variations - Yingkai Ma; Zhilin Liu; Ting Wang; Simeng Song; Jing Xiang; Xiaoyue Zhang (Ocean Engineering, 2024)

Imidacloprid triggered changes in strawberry fruits on edible quality and phenolic profiles by applied at two growth stages - Ning Yue; Chen Zhang; Simeng Li; Hongping Wang; Xiaohui Li; Xueying Chen; Fen Jin (Food Research International, 2024)

Quantifying physiological contributions to yield loss in response to planting date in short-season cotton under a cotton wheat double-cropping system - Simeng Guo; Yingchun Han; Guoping Wang; Fengqi Wu; Yaoyu Jia; Jiale Chen; Xiaofei Li; Wenli Du; Yabing Li; Lu Feng (European Journal of Agronomy, 2024)

Intelligence detection of oil absorption in French fries by surface profiles - Simeng Wang; Shuli Zhao; Nan Wang; Qianru Lu; Haile Zhao; Ying Liu; Jinwei Li; Liuping Fan (Food Research International, 2024)

Zinc Oxide Nanoparticles Induce Renal Injury by Initiating Oxidative Stress, Mitochondrial Damage and Apoptosis in Renal Tubular Epithelial Cells - Shuang Liu; Han Zhou; Yang Shi; Simeng Yi; Xinyu Wang; Jingyan Li; Bin Liao; Jimin Cao; Guang Li (Biological Trace Element Research, 2024)

EMPMR berthing scheme: A novel event-triggered motion planning and motion replanning scheme for unmanned surface vessels - Shouzheng Yuan; Zhilin Liu; Yuxin Sun; Simeng Song; Zhongxin Wang; Linhe Zheng (Ocean Engineering, 2023)

Implementation of a direct-addressing based lattice Boltzmann GPU solver for multiphase flow in porous media - Guang Yang; Yu Chen; Simeng Chen; Moran Wang (Computer Physics Communications, 2023)

Fuzzy composite risk assessment of water-energy-food-carbon nexus in the dispark pumped irrigation system - Simeng Cui; Jianyun Zhang; Xiaojun Wang; Mengyang Wu; Xinchun Cao (Journal of Hydrology, 2023)

5-Methoxytryptophan ameliorates endotoxin-induced acute lung injury in vivo and in vitro by inhibiting NLRP3 inflammasome-mediated pyroptosis through the Nrf2/HO-1 signaling pathway - Yang Ma; Zhixue Wang; Xiaoyang Wu; Zijian Ma; Jia Shi; Simeng He; Shaona Li; Xiangyun Li; Xiangkun Li; Yan Li; Jianbo Yu (Inflammation Research, 2023)

Nitrogen stress alters trade-off strategies between reproduction and vegetative growth in soybean - Menglong Bu; Yue Li; Simeng Wang; Changjiang Huang; Chuansheng Wu; Shuai Liu (Brazilian Journal of Botany, 2023)

Insight into influence of process parameters on co-pyrolysis interaction between Yulin coal and waste tire via rapid infrared heating - Yuxin Wen; Simeng Liu; Shihao Fu; Zhiheng Wang; Haoquan Hu; Lijun Jin (Fuel, 2023)

Changes in within-boll yield components explain cotton yield and quality variation across planting dates under a double cropping system of cotton-wheat - Simeng Guo; Taijie Liu; Yingchun Han; Guoping Wang; Wenli Du; Fengqi Wu; Yabing Li; Lu Feng (Field Crops Research, 2023)

Microbiome-metabolomics analysis insight into the effects of dietary resistant starch on intestinal integrity - Simeng Qin; Keying Zhang; Xuemei Ding; Shiping Bai; Jianping Wang; Gang Tian; Yue Xuan; Zhuowei Su; Quifeng Zeng (Food Chemistry, 2023)

Comparative analysis of nitrate evolution patterns during pollution episodes: Method development and results from Tianjin, China - Yafei Li; Yan Han; Simeng Ma; Yufen Zhang; Haoqi Wang; Jingyi Yang; Lu Yao; Xiaohui Bi; Jianhui Wu; Yinchang Feng (Science of The Total Environment, 2023)

Histone modification in podocyte injury of diabetic nephropathy - Simeng Wang; Xinyu Zhang; Qinglian Wang; Rong Wang (Journal of Molecular Medicine, 2022)

The effects of temperature variability on mortality in patients with chronic obstructive pulmonary disease: a time-series analysis in Hangzhou, China - Simeng Gu; Xiaofeng Wang; Guangming Mao; Xuemin Huang; Yuanyang Wang; Peiwei Xu; Lizhi Wu; Xiaoming Lou; Zhijian Chen; Zhe Mo (Environmental Science and Pollution Research, 2022)

Green energy mismatch, industrial intelligence and economics growth: theory and empirical evidence from China - Yunwei Li; Qiuping Ji; Zijie Wang; Zishan Xiong; Simeng Zhan; Yiping Yang; Yu Hao (Environment, Development and Sustainability, 2022)

NEK7: a new target for the treatment of multiple tumors and chronic inflammatory diseases - Jin Wang; Simeng Chen; Min Liu; Min Zhang; Xiaoyi Jia (Inflammopharmacology, 2022)

TMEM92 acts as an immune-resistance and prognostic marker in pancreatic cancer from the perspective of predictive, preventive, and personalized medicine - Simeng Zhang; Xing Wan; Mengzhu Lv; Ce Li; Qiaoyun Chu; Guan Wang (EPMA Journal, 2022)

The microbiota–gut–brain axis: A novel nutritional therapeutic target for growth retardation - Ming Qi; Bie Tan; Jing Wang; Simeng Liao; Yuankun Deng; Peng Ji; Tongxing Song; Andong Zha; Yulong Yin (Critical Reviews in Food Science and Nutrition, 2022)

Metabolomics changes in brain-gut axis after unpredictable chronic mild stress - Qiuyue Xu; Mingchen Jiang; Simeng Gu; Xunle Zhang; Guangkui Feng; Xianjun Ma; Shijun Xu; Erxi Wu; Jason H Huang; Fushun Wang (Psychopharmacology, 2022)
Background Major depressive disorder is a leading cause of disability worldwide, affecting up to 17 % of the general population. The neural mechanisms of depression, however, are yet to be uncovered. Recently, attention has been drawn to the effects of dysfunctional brain-gut axis on depression, and many substances have been suggested to be involved in the communication between the gut and brain, such as ghrelin. Methods We herein systematically examined the changes of metabolomics after unpredictable chronic mild stress (UCMS)–induced depression-like behaviors in rats and compared the altered metabolites in the hippocampus and jejunum samples. Results Our results show that many metabolites significantly changed with UCMS both in the hippocampus and jejunum, such as L-glutamine, L-tyrosine, hydroxylamine, and 3-phosphoglyceric acid. Further studies suggested that these changes are the reasons for anxiety-like behaviors and depression-like behaviors in UCMS rats and also are the reasons for hippocampal neural plasticity. Conclusions Coexistence of brain and gut metabolic changes in UCMS-induced depressive behavior in rats suggests a possible role of brain-gut axis in depression. This study provides insights into the neurobiology of depression.

Temporal trends and source apportionment of water pollution in Honghu Lake, China - Shuai Chen; Simeng Wang; Yanxi Yu; Mingjun Dong; Yanqiang Li (Environmental Science and Pollution Research, 2021)

Pressure-induced structural transition and metallization in MnSe2 - Baoyun Wang; Xiaoning Wang; Simeng Wang; Dayong Tan; Wansheng Xiao; Wen Liang; Maoshuang Song (Physics and Chemistry of Minerals, 2020)

Antibacterial activity of ruthenium polypyridyl complexes against Staphylococcus aureus and biofilms - Simeng Bu; Guijuan Jiang; Guangbin Jiang; Jinyao Liu; Xiaoli Lin; Jihong Shen; Yanshi Xiong; Xuemin Duan; Jintao Wang; Xiangwen Liao (JBIC Journal of Biological Inorganic Chemistry, 2020)

FRZB1 rs2242070 polymorphisms is associated with brick tea type skeletal fluorosis in Kazakhs, but not in Tibetans, China - Yanmei Yang; Qiaoshi Zhao; Yang Liu; Xiaona Liu; Yanru Chu; Huazhu Yan; Yumei Fan; Simeng Huo; Limei Wang; Qun Lou; Ning Guo; Dianjun Sun; et al. (Archives of Toxicology, 2018)

Erratum to: The role of particle size of glyburide crystals in improving its oral absorption - Wenqian Yang; Yongjun Wang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

The role of particle size of glyburide crystals in improving its oral absorption - Yongjun Wang; Wenqian Yang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

NKCC1 up-regulation contributes to early post-traumatic seizures and increased post-traumatic seizure susceptibility - Fushun Wang; Xiaowei Wang; Lee A. Shapiro; Maria L. Cotrina; Weimin Liu; Ernest W. Wang; Simeng Gu; Wei Wang; Xiaosheng He; Maiken Nedergaard; Jason H. Huang (Brain Structure and Function, 2017)

Ionizing radiation stimulates octamer factor DNA binding activity in human carcinoma cells - Rachel L. Meighan-Mantha; Anna T. Riegel; Simeng Suy; Violaine Harris; Fuh-Han Wang; Christopher Lozano; Theresa L. Whiteside; Usha Kasid (Molecular and Cellular Biochemistry, 1999)